Wind Resource Assessment in Complex Urban Environment. Issue 2 (April 2015) - Romanić, Djordje; Rasouli, Ashkan; Hangan, Horia
A wind energy assessment methodology is proposed for urban environments and applied for a specific urban development. Micro-scale wind energy maps are created using computational fluid dynamics simulations. The wind maps are used to calculate the available wind energy for the 2015 Pan American Games Athletes' Village, in Toronto, Canada. The structure of the urban boundary layer has also been analyzed. It is shown that the maximum available energy can cover an important ratio of typical power requirements for the buildings. However, it is found that existing wind turbines have power curves that are de-coupled from the probability density functions of the wind availability. Therefore, the need for designing new urban wind turbines is discussed and required specifications are highlighted.